2021
DOI: 10.1038/s41598-021-91320-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective estrogen receptor modulator lasofoxifene suppresses spondyloarthritis manifestation and affects characteristics of gut microbiota in zymosan-induced SKG mice

Abstract: Ankylosing spondylitis is a male-predominant disease and previous study revealed that estrogens have an anti-inflammatory effect on the spondyloarthritis (SpA) manifestations in zymosan-induced SKG mice. This study aimed to evaluate the effect of selective estrogen receptor modulator (SERM) lasofoxifene (Laso) on disease activity of SpA. Mice were randomized into zymosan-treated, zymosan + 17β-estradiol (E2)-treated, and zymosan + Laso-treated groups. Arthritis was assessed by 18F-fluorodeoxyglucose (18F-FDG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In 2017, Hyemin Jeong et al reported that estrogen could attenuate the spondylarthritis manifestations of the SKG arthritis model 70 . Later, they also applied selective estrogen receptor modulator lasofoxifene to suppress joint inflammation and enhance bone mineral density in zymosan-induced SKG mice 71 . Furthermore, oral estrogen therapy in female patients and human chorionic gonadotrophin injections in male patients with AS could result in a moderate clinical improvement 72 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Hyemin Jeong et al reported that estrogen could attenuate the spondylarthritis manifestations of the SKG arthritis model 70 . Later, they also applied selective estrogen receptor modulator lasofoxifene to suppress joint inflammation and enhance bone mineral density in zymosan-induced SKG mice 71 . Furthermore, oral estrogen therapy in female patients and human chorionic gonadotrophin injections in male patients with AS could result in a moderate clinical improvement 72 .…”
Section: Discussionmentioning
confidence: 99%
“…One report proposed ostrogens might reduce arthritis due to their suppression of wnt signalling [72]. Another study reported that selective oestrogen receptor modulator (SERM) lasofoxifene not only suppresses the effects of joint inflammation and improves bone mineral density in SKG mice, but it also affected the composition and biodiversity of the gut microbiome, with the authors concluding further reaserch on the role of SERMS to evaluate their effects in SpA is required [73].…”
Section: Sex Hormonesmentioning
confidence: 99%
“…There is literature to suggest a relationship between women who experience excess androgen levels in conditions such as polycystic ovarian syndrome (PCOS) and development of AS [74], as well as other rheumatic diseases [75]. A Korean study questioned whether other factors besides sex hormones play a role in reduced disease progression in females noting in their study there was no significant relationship between oestrogen levels and radiographic progression [73].…”
Section: Sex Hormonesmentioning
confidence: 99%
“… 20 Previously, SERMs have been reported to modulate inflammation in animal models of IBD, 21 , 22 autoimmune encephalomyelitis, 23 , 24 and ankylosing spondylitis. 25 Additionally, clinical data suggests that tamoxifen may decrease C‐reactive protein levels in healthy females. 26 …”
Section: Introductionmentioning
confidence: 99%